2017
DOI: 10.3171/2016.8.jns16899
|View full text |Cite
|
Sign up to set email alerts
|

Elevated preoperative neutrophil-to-lymphocyte ratio as a predictor of worse survival after resection in patients with brain metastasis

Abstract: B rain metastases occur in 10% to 40% of patients with cancer and are the most common central nervous system neoplasm in adults. 28,33 With increased surveillance, improved control of systemic cancer, and prolonged survival, the incidence of patients with brain metastases is increasing. 17 The management of brain metastases has been revolutionized in clinical oncology by 4 developments: improved brain imaging, improved management of systemic diseases, the distribution of stereotactic irradiation, and the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…Two prior studies [33, 34]—have specifically investigated the association between inflammatory markers and OS in patients with BM, albeit without assessing simultaneous corticosteroid use. Shaverdian et al [33] demonstrated that pre-treatment markers, including platelet count and albumin count, were associated with OS in 70 patients with BM, but not the NLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prior studies [33, 34]—have specifically investigated the association between inflammatory markers and OS in patients with BM, albeit without assessing simultaneous corticosteroid use. Shaverdian et al [33] demonstrated that pre-treatment markers, including platelet count and albumin count, were associated with OS in 70 patients with BM, but not the NLR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they only included BM due to breast, melanoma or non-small cell lung cacncer (NSCLC). Mitsuya et al [34] focused on resected BM: in a cohort of 105 patients, they found that NLR < 5 was associated with improved OS. Systemic therapy use, however, was significantly higher in the cohort with NLR < 5: 55 vs. 17%.…”
Section: Discussionmentioning
confidence: 99%
“…A number of highly significant associations were found between neutrophils and the response to therapy of brain malignancies [91,102]. Furthermore, numerous reports point to the negative prognostic value of neutrophil presence and their participation in neuroinflammation in the milieu of brain tumors [91,93,[102][103][104][105]. As noted above, current evidence only indirectly points to the participation of NETs in the biology of primary and secondary brain tumors, and we must acknowledge that this issue has not been thoroughly studied yet.…”
Section: May Nets Play a Role In The Development Of Brain Tumors?mentioning
confidence: 93%
“…These observations are reminiscent of what has been shown in other metastatic organs that are not subject to immune privilege (Casbon et al, 2015; Coffelt et al, 2015; Liu et al, 2016; Wculek and Malanchi, 2015), supporting the concept that in the context of a tumor, the brain may be aberrantly exposed to pathologic inflammation that influences disease progression. Moreover, from a prognostic standpoint, a high ratio of neutrophils to lymphocytes in the peripheral blood is associated with reduced survival time, including following surgical resection, for both brain metastasis and glioblastoma patients (Bambury et al, 2013; McNamara et al, 2014; Mitsuya et al, 2016). It will therefore be imperative going forward to develop a more complete understanding of how the brain microenvironment changes in response to a primary tumor outside the CNS, in an analogous manner to what has been shown for other secondary organs such as lung or liver.…”
Section: Introductionmentioning
confidence: 99%
“…DC vaccinations such as DCVax-L have shown promising results, and as a consequence are in advanced clinical trials (newly-diagnosed glioblastoma, NCT00045968, Phase III) (Prins et al, 2011). Neutrophils also hold potential for their prognostic value in patients with primary brain tumors (Bertaut et al, 2016; Fossati et al, 1999), and metastatic disease (Koh et al, 2016; Mitsuya et al, 2016; Serdarevic et al, 2016). Targeting the vasculature through anti-angiogenic strategies is also relevant in glioblastoma patients given that this tumor type is highly vascularized; however, the current evidence seems to suggest that these strategies may be optimally used in the recurrent setting in combination with additional therapies (Friedman et al, 2009; Kreisl et al, 2009), rather than as frontline monotherapy on newly diagnosed, untreated disease (Gilbert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%